Humorous Potential of Board Games for Children of Senior Preschool Age - Rudenskyi, Rostyslav; Pysarchuk, Oksana; Shcherbiak, Iurii; Akimjaková, Beáta; Minarovicova, Katarina (Journal of Education Culture and Society, 2024)
Aim. The aim of the study is to determine the humorous potential of modern board games for senior preschool children which are used in preschool education institutions. Methods. The aims were achieved through the implementation of methods: theoretical (analysis of the psycho-pedagogical, philosophical and source base in the field of game design and children’s game theory), empirical (observation of the game process of children with board games, combined analysis of board game sets from different countries) and comprehensive analysis of board game sets for children. Results. It has been determined that the humorous potential can be expressed through each structural component of a board game: content (plot, characters and rules), conventional graphic plan (images, symbols, icons, colour, reality and conventionality of the image), equipment (character chips, character figures, tokens, field etc.). It has been proved that humour is a social and game construct of the modern theory and practice of game design. Conclusion. It has been concluded that the humorous potential of board games for children has a significant developmental effect in the organisation of game activities. The use of humorous board games provides a positive microclimate in the team, promotes the development of emotional intelligence in children, enriches their cognitive and sensory experience. Humorous board games can be used both for organising the education of older preschool children, preparing them for school, and for organising recreation, leisure, and raising children’s play culture.